Balanced assessment improving student achievement and standardized test result - Johnson, Todd; Brittner, Ilana; Association for Supervision and Curriculum Development (Alexandria, VA : ASCD, 2004)
This program provides information regarding the assessment of students in order to improved achievement and standardized test results. Expalining on assessment comprehensive approach, assessment tools and also relative assessment
program 1. A comprehensive approach (37 min.) -- program 2. Using a range of assessment tools (25 min.) -- program 3. Relative assessment (27 min.)
Title from title screen
Editor, Ilana Brittner, Dave Brittner ; graphic, Frank McIntyre ; director of photography, Dave Brittner
Keywords: Educational tests and measurements; Academic achievement